Legal Education and Legal Culture in Times of Globalisation - Gonzales Mantilla, Gorki (2007)
This article provides a critical view of the evolution of law teaching in a context such as globalisation. To that extent, the author mentions how the reform of teaching at the Faculty of Law of the PUCP was initiated. From this, it was expected that the reform in legal education should be able to respond to social demands and contribute to the correct training of students, as well as provide the necessary resources to implement new legal specialisations in the light of the Peruvian social reality. In this way, the author argues that globalisation demands that the new generations break with the traditional paradigms of law teaching, which for a long time focused on a formalist and dogmatic formation of law. The author suggests a new way of teaching law, with the aim of training professionals who can understand and operate in a dynamic legal environment. This implies the need to integrate an interdisciplinary, comparative and practical vision into the curriculum of law schools, in order to develop the necessary skills to function in this new context.